Characteristic analysis and optimisation of an asymmetric‐primary axial‐flux hybrid‐excitation generator for vertical‐axis wind turbines. Issue 10 (15th June 2022) - Liu, Jing; Huang, Lei; Zhang, Qiang; Chen, Jiming
Abstract: Axial‐flux wind generators have advantages of high ratio of generator diameter to generator length and high possibility of modular construction, which make them suitable for use in vertical‐axis wind turbines. The design optimisation and analysis of an asymmetric‐primary axial‐flux hybrid‐excitation generator that can provide a controllable suspension magnetic levitation force to compensate for the ripple of axial force fluctuation are described. First, the mechanical topological operation principle of the proposed generator is introduced, and four generators with different magnetic field modulation ratios and winding distributions are investigated. Second, the levitation force and the torque model are based on the d/q axes dynamic mathematical model. Four generators are compared based on no‐load performance. Considering the polar arc coefficient, this study analyzes the no‐load performance. In addition, comprehensive analyses of the on‐load performance under two typical load conditions are conducted. Based on simulation results and by integrating the magnetic field modulation ratio, tooth width, and permanent magnet thickness, the optimal design of a 12s22p generator is obtained. Finally, a prototype of the 12s22p generator is manufactured and tested in a laboratory situation under on‐load and no‐load conditions. All of the findings are consistent with the simulation results.